Neural mechanisms of symmetry perception: hemispheric specialization and the impact of noise on reflection symmetry detection - Wang, Meng; Yang, Jingjing; Yu, Yiyang; Wu, Qiong; Wu, Fengxia (Frontiers in Neuroscience, 2025)
Symmetry is a crucial cue for perceptual grouping in human vision. This study investigates the neural and cognitive mechanisms underlying symmetry perception, focusing on hemispheric specialization and the effects of noise on symmetry detection. Using psychophysical and electrophysiological (EEG) experiments, participants were presented with reflection symmetric patterns (full circle vs. right-left quarter-circle), under varying noise levels. Behavioral results demonstrated noise-induced impairment in accuracy (p < 0.001), with Cycle outperforming Quarter in noiseless conditions (p < 0.05), highlighting the role of contour completeness in perceptual grouping. EEG recordings revealed distinct neural mechanisms associated with different stages of symmetry processing. Early sensory processing exhibited left-hemisphere dominance, while later stages implicated the right hemisphere in noise-modulated global integration. Noise disrupted early contour integration and attenuated higher-order object recognition processes, with right-hemisphere sensitivity to noise emerging during decision-making. These findings challenge the strong version of the callosal hypothesis, highlighting the complexity of hemispheric interactions in symmetry perception. This study provides new insights into the interplay between bottom-up sensory processing and top-down hemispheric interactions in perceptual organization.